REALISTIC INTERPRETATION OF CONDITION FACTOR USING STOMACH CONTENT ANALYSIS OF Clarias gariepinus IN GWALLAGA RIVER, BAUCHI – NIGERIA - ABDULKARIM, M.; YUSUF, Z. A.; MISAU, A. B.; GARBA, A. M.; MAHMOOD, S. (Nigerian Journal of Fisheries, 2018)
The predictive power of condition factor (k) as a biomathematical model (BM) was investigated using a case study of stomach content analysis (SCA) of Clarias gariepinus in Gwallaga River, Bauchi, Nigeria. The river was divided into four stations: Headwater (A), Upper middle (B), Lower middle (C) and Tail water (D). Ten fish were caught fortnightly from each station during the dry season. Eighty fish were collected during the period of the research. Lengths and weights of the fish were measured. The fish were dissected, stomach contents were identified. The stomach repletion levels (SRL) were categorized into five (0, 25, 50, 75 and 100%). The SCA of C. gariepinus revealed Phytoplankton had the highest importance index of 489.3273 out of the seven feed items. X 2 = 26.078 (P > 0.05) showed that there is an association between SRL of the fish and their stations. This was supported by the high k-value of fish from station A (k = 1.1889) but fish from other stations had low k-values with observed low SRL. It was concluded that this research has realistically tested the predictive power of k as a BM through SCA because nutrition contributes strongly to the physiological well-being of an organism.